(untitled) (Global Journal of Management and Business Research, 2023)
This article sheds light on the specificities of necessity entrepreneurship characterized by the concern to reduce the risk of sinking and disappearing in contrast to opportunity entrepreneurship which is based on a secure present and the willingness to take risks for a promising future It examines the emergence and valorization of necessity entrepreneurship with a focus on the case of women in the Republic of Congo The article highlights key issues related to this form of entrepreneurship